2009
DOI: 10.1091/mbc.e09-05-0389
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian pre-mRNA 3′ End Processing Factor CF Im68 Functions in mRNA Export

Abstract: Export of mRNA from the nucleus is linked to proper processing and packaging into ribonucleoprotein complexes. Although several observations indicate a coupling between mRNA 3 end formation and export, it is not known how these two processes are mechanistically connected. Here, we show that a subunit of the mammalian pre-mRNA 3 end processing complex, CF I m 68, stimulates mRNA export. CF I m 68 shuttles between the nucleus and the cytoplasm in a transcription-dependent manner and interacts with the mRNA expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 50 publications
0
69
0
Order By: Relevance
“…Also, several previous studies suggest a coupling between the polyadenylation machinery and mRNA export in mammalian cells (for review, see Zhao et al 1999). More recently, the CPSF6 gene product (the CF I m 68 protein) was reported to stimulate Nxf1-mediated mRNA export (Ruepp et al 2009). It was suggested that the CF I m 68 protein accompanies the RNP complex to the cytoplasm and that it is released in the cytoplasm during the initial stages of translation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several previous studies suggest a coupling between the polyadenylation machinery and mRNA export in mammalian cells (for review, see Zhao et al 1999). More recently, the CPSF6 gene product (the CF I m 68 protein) was reported to stimulate Nxf1-mediated mRNA export (Ruepp et al 2009). It was suggested that the CF I m 68 protein accompanies the RNP complex to the cytoplasm and that it is released in the cytoplasm during the initial stages of translation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that members of the cleavage and polyadenylation complex are involved in the processing of histone pre-mRNA in addition to their role in the cleavage and polyadenylation of cellular mRNA (7,23,40,49,51). Moreover, a recent proteomic analysis of the cleavage and polyadenylation complex found the presence of several Integrator proteins (45).…”
Section: Figmentioning
confidence: 97%
“…CFI m is composed of a large subunit of 59, 68, or 72 kDa and a small subunit of 25 kDa (CFI m 25, also referred to as CPSF5 or NUDT21) (12,13), both of which contribute to RNA binding (14). The large subunit, encoded by either of two paralogs (CPSF6 and CPSF7), contains an N-terminal RNA Recognition Motif (RRM), an internal polyproline-rich region, and a C-terminal RS/RD alternating charge domain-a structure similar to that of the SR-protein family of splicing regulators.…”
mentioning
confidence: 99%